ANALISIS TINGKAT KESEHATAN UNIT SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (USPPS) KOPERASI SYARIAH BMT AL-KAROMAH MARTAPURA - Hayati, Laila; Rusdiana, Rusdiana; Rizqiani3, Hu’shila Awalia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
The health assessment (PENKES) of Islamic savings and loan cooperatives and Islamic savings and loan and financing units (KSPPS/USPPS) of cooperatives is an assessment to measure the soundness of Islamic savings and loan and Islamic financing cooperatives and Islamic savings and loan units and cooperative financing on a periodic or incidental basis. Assessment of the health of cooperatives is very important to do, to find out more about the condition of cooperatives in terms of financial health, management and compliance with sharia principles. So the purpose of this research is to analyze the soundness of the sharia savings and loan and financing unit (USPPS) of the BMT Al-Karomah Martapura sharia cooperative in 2021. This type of research is qualitative research (Qualitative study). And including field research, using descriptive analysis with an inductive mindset. The subject studied was the Manager of the BMT Al-Karomah Martapura Sharia Cooperative. While the object is the soundness level of the Islamic savings and loan and financing unit (USPPS) of the BMT Al-Karomah Martapura Sharia Cooperative in 2021, covering all aspects of the health assessment, namely: aspects of capital, productive asset quality, management, efficiency, liquidity, cooperative identity, independence and growth, as well as compliance with Sharia Principles. The analysis follows the guidelines issued by the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises No. 07/Per/Dep.6/IV/2016. The results showed that the health level of the savings and loan and sharia financing unit (USPPS) of the BMT Al-Karomah Martapura Sharia Cooperative in 2021 was in the Fairly Healthy predicate with a total score of 74,80. From the predicate obtained as a whole on the aspects of financial health, management and compliance with sharia principles, they are already in a fairly good health condition.